2018
DOI: 10.1080/10401334.2018.1478731
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Italian Students’ Responses to Professional Dilemmas: A Cross-Cultural Comparison

Abstract: Phenomenon: Medical professionalism is a complex construct, based in social and cultural influences, yet little research has been done to show how culture influences the behaviors and attitudes of medical students. We presented Italian students with the same professional dilemmas used in a previous Canadian and Taiwanese cross-cultural study to look for similarities and differences and detect elements of Italian culture that influenced how students responded to dilemmas. The aim was to provide medical educator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Although the influence of sociocultural values was present in other articles, 65,83 the impact of society on PIF was most clearly seen in the work of Helmich et al, 58 who contrasted conceptualisations of PIF in Taiwanese and Dutch medical students. This article elucidated how cultural constructs of what it means to be a physician and patient autonomy lead to different professional identities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the influence of sociocultural values was present in other articles, 65,83 the impact of society on PIF was most clearly seen in the work of Helmich et al, 58 who contrasted conceptualisations of PIF in Taiwanese and Dutch medical students. This article elucidated how cultural constructs of what it means to be a physician and patient autonomy lead to different professional identities.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included various contexts previously identified in health education research 82 (eg, longitudinal clerkships, social media, patient care, dual professions, etc.) and only two included the participants’ cultural context as an important consideration in their analysis 58,83 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations